Pengaruh Analisis Fundamental terhadap Harga Saham Syariah Yang Tergabung di Jakarta Islamic Index (JII) - Estefania Graciela; Marlina Laia; Munawarah Munawarah (Politeknik Ganesha Medan, 2021)
This research was conducted in order, so we can find out how much influence the variable x on variable y. The independent variable (x) on this research are Earning Per Share, Book Value, Debt to Asset Ratio, Debt to Equity Ratio, Net Profit Margin and the variable y is Sharia Stock Prices listed on the Jakarta Islamic Index (JII). This research used the form of annual financial reports published by companies on the Indonesia Stock Exchange website. The total sample is 30 companies. The final number in this research is 16 companies between 2015 until 2018. And the data analysis used multiple linear regression, namely simultaneous (F test), partial (T-test), and Least Squares Equation. And the result of the fundamental factors are Earning Per Share, Book Value, Debt to Asset Ratio, Debt to Equity Ratio, Net Profit Margin has an effect of 70,1% on Sharia Stock Prices. While the rest, namely 29,9% is influenced by other factors. Then the partially fundamental factors are Earning Per Share, Book Value, Net Profit Margin has a significant effect on the Sharia Stock Prices, and fundamental factors are Debt to Asset Ratio, Debt to Equity Ratio doesn’t have a significant effect on Sharia Stock Prices.